Seismic source characteristics of the intraslab 2017 Chiapas-Mexico earthquake (Mw8.2) - Jiménez C. (2018)
This research was sponsored in part by the Vice-rectorate for Research and Postgraduate from “Universidad Nacional Mayor de San Marcos”, by CONCYTEC through the Teacher-Researcher bonus and by the “Direccion de Hidrografia y Navegacion” from the Peruvian Navy. In addition, we acknowledge the anonymous reviewers for their valuable comments and observations.